2022
DOI: 10.1002/pol.20210938
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembled monolayers for interface engineering in polymer solar cells

Abstract: Polymer solar cell (PSC) has been developed vastly in the past decade due to the advantages of low cost, lightweight, mechanical flexibility, versatility of chemical design and synthesis, semitransparency, and solution processing. The performance and lifetime of PSCs are highly dependent on the properties of both active materials and their interfaces. The combination of the versatility of organic chemistry and the multitude of well-understood ligand-metal interactions allows self-assembled monolayers (SAMs) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 117 publications
0
21
0
1
Order By: Relevance
“…The high WF with appropriate modification could provide Ohmic contact at the active layer/ITO interfaces to ensure the efficient charge extraction for high short‐circuit current density ( J SC ) and fill factor (FF) and realize maximum open‐circuit voltage ( V OC ). [ 20 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The high WF with appropriate modification could provide Ohmic contact at the active layer/ITO interfaces to ensure the efficient charge extraction for high short‐circuit current density ( J SC ) and fill factor (FF) and realize maximum open‐circuit voltage ( V OC ). [ 20 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 3,19 ] As alternatives, self‐assembly monolayers (SAMs) of organic small molecules with different dipoles are another attractive alternative for indium tin oxide (ITO) modification to reduce the barrier at ITO/active layer interface with tunable interface properties to achieve high‐performance PSCs. [ 20–22 ] For example, Anthopoulos et al demonstrated a high PCE of 16.6% based on [2‐(9 H‐carbazol‐9‐yl)ethyl]phosphonic acid (2PACz)‐modified ITO (ITO‐2PACz) and poly[(2,6‐(4,8‐bis(5‐(2‐ethylhexyl‐3‐fluoro)thiophen‐2‐yl)‐benzo[1,2‐b:4,5‐b′]‐dithiophene))‐alt‐(5,5‐(1′,3′‐di‐2‐thienyl‐5′,7′‐bis(2‐ethylhexyl)benzo[1′,2′‐c:4′,5′‐c′]dithiophene‐4,8‐dione)] (PM6):N3 active layer due to the high work function (WF) of ITO‐2PACz (5.45 eV) and the nanofiber structure of active layer deposited on ITO‐2PACz. This is higher than PCEs of bare ITO (6.45%) and ITO/PEDOT:PSS–based (15.94%) devices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the stability of such devices has not yet been fully investigated. [26] Finally, Xu et al have reported devices exhibiting better performances and stability using a new, less acidic, and solution-processable polymer called PCPDT-2Ph-H. [27] Here we demonstrate the fabrication of a solution-processed conventional (p-i-n) OPV structure embedding an HTL consisting of the same polymer used in the active layer: Poly[[6,7-difluoro[(2-hexyldecyl)oxy]-5,8-quinoxalinediyl]-2,5-thiophenediyl] (PTQ10, Figure 1a), a recent major polymer candidate for OPV with simplified chemical structure and lower cost synthesis. [28] Against the rules of solvent orthogonality, we show that coating the polymer:non-fullerene-acceptor (NFA) BHJ on top of the HTL consisting of doped PTQ10 is feasible.…”
Section: Introductionmentioning
confidence: 99%